2009
DOI: 10.3892/mmr_00000224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythropoietin on human tumor growth in xenograft models

Abstract: Abstract. recombinant human erythropoietin (rhePo) has been used in the eu and the united States for the treatment of anemia in cancer patients after myelosuppressive chemotherapy or radiotherapy. However, several conflicting results have been reported concerning the detrimental effect of rhEPO on survival benefit in cancer patients. In experimental studies, contradictory results were also reported in in vitro tumor cell proliferation studies and in vivo tumor growth studies using tumor cells expressing EPO-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
2
3
Order By: Relevance
“…Indeed, some in vitro studies have demonstrated that Epo enhances tumor proliferation [Westenfelder and Baranowski, ; Acs et al, ; Yasuda et al, ; Feldman et al, ]. However, others have demonstrated that no effects of Epo on tumor growth were observed in vitro [Dunlop et al, ; Jeong et al, ], and in vivo [Kataoka et al, ]. Our current study failed to reveal any stimulatory effects of Epo on tumor growth, however, we did find that Epo inhibits PCa cell apoptosis.…”
Section: Discussioncontrasting
confidence: 67%
“…Indeed, some in vitro studies have demonstrated that Epo enhances tumor proliferation [Westenfelder and Baranowski, ; Acs et al, ; Yasuda et al, ; Feldman et al, ]. However, others have demonstrated that no effects of Epo on tumor growth were observed in vitro [Dunlop et al, ; Jeong et al, ], and in vivo [Kataoka et al, ]. Our current study failed to reveal any stimulatory effects of Epo on tumor growth, however, we did find that Epo inhibits PCa cell apoptosis.…”
Section: Discussioncontrasting
confidence: 67%
“…However, those results are in conflict with results from other groups who reported no effect on the same pathways using the same or similar cell types 80,91,223,232,233,259,285. Interestingly, there are several reports where rHuEpo had no effects on phosphorylation of JAK2 or STAT5, but did have effects on ERK phosphorylation 271,272,276,284,286288.…”
Section: Is Functional Epor Expressed In Tumor Cells?contrasting
confidence: 59%
“…Furthermore, EPO may exert indirect effects on T cell functions via Ter cells and Ter cell-produced ARTN, such as diminished tumor cell killing capacity by T cells. These findings implicate an indirect effect of EPO on cancer treatment outcomes, which differs from previous studies that focused on the direct action of EPO on tumor cells (62).…”
Section: Discussioncontrasting
confidence: 99%